Sustainable green approach to synthesize Fe3O4/α-Fe2O3 nanocomposite using waste pulp of Syzygium cumini and its application in functional stability of microbial cellulases - Srivastava N.; Srivastava M.; Alhazmi A.; Mohammad A.; Khan S.; Pal D.B.; Haque S.; Singh R.; Mishra P.K.; Gupta V.K. (My University, 2025)
Synthesis of nanomaterials following green routes have drawn much attention in recent years due to the low cost, easy and eco-friendly approaches involved therein. Therefore, the current study is focused towards the synthesis of Fe3O4/α-Fe2O3 nanocomposite using waste pulp of Jamun (Syzygium cumini) and iron nitrate as the precursor of iron in an eco-friendly way. The synthesized Fe3O4/α-Fe2O3 nanocomposite has been extensively characterized through numerous techniques to explore the physicochemical properties, including X-ray diffraction, Fourier transform infrared spectroscopy, Raman spectroscopy, Ultraviolet-Vis spectroscopy, field emission scanning electron microscope, high resolution transmission electron microscope and vibrating sample magnetometer. Further, efficiency of the Fe3O4/α-Fe2O3 nanocomposite has been evaluated to improve the incubation temperature, thermal/pH stability of the crude cellulase enzymes obtained from the lab isolate fungal strain Cladosporium cladosporioides NS2 via solid state fermentation. It is found that the presence of 0.5% Fe3O4/α-Fe2O3 nanocomposite showed optimum incubation temperature and thermal stability in the long temperature range of 50–60 °C for 15 h along with improved pH stability in the range of pH 3.5–6.0. The presented study may have potential application in bioconversion of waste biomass at high temperature and broad pH range. © 2021, The Author(s).